2009
DOI: 10.1007/s11845-009-0359-8
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the reporting and management of needlestick injuries among surgeons

Abstract: Most surgeons and trainees do not report all their needlestick injuries to occupational health despite many reporting injury related anxiety. The process is felt to take too long and the perceived risk of viral transmission is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 11 publications
2
19
1
10
Order By: Relevance
“…Guidance from the General Medical Council (GMC) suggests that 'a relative or friend of the patient may be an acceptable chaperone' contrary to the recommendations of the Ayling Inquiry that chaperones should not be friends or relatives of the patient. 1,2 Significantly for medicolegal implications, we found that 74% of doctors did not document chaperone use. GMC guidance recommends that doctors 'should record any discussion about chaperones and its outcome', advice reiterated by the Medical Defence Union.…”
mentioning
confidence: 85%
“…Guidance from the General Medical Council (GMC) suggests that 'a relative or friend of the patient may be an acceptable chaperone' contrary to the recommendations of the Ayling Inquiry that chaperones should not be friends or relatives of the patient. 1,2 Significantly for medicolegal implications, we found that 74% of doctors did not document chaperone use. GMC guidance recommends that doctors 'should record any discussion about chaperones and its outcome', advice reiterated by the Medical Defence Union.…”
mentioning
confidence: 85%
“…A identificação da prevalência de subnotificação dos acidentes com material biológico nas instituições de saúde constitui um desafio, visto que depende da informação fornecida pelo próprio profissional envolvido. Assim, utilizamos o questionário para a obtenção de dados acerca da população-alvo, uma ferramenta que tem sido amplamente aplicada em estudos envolvendo acidentes ocupacionais 12,[18][19][20][21] . No presente estudo, a maioria das vítimas de acidente ocupacional era do gênero feminino e da categoria "auxiliares de Enfermagem".…”
Section: Discussionunclassified
“…Observa-se na literatura que os questionários auto-aplicados vêm sendo amplamente utilizados para a obtenção de dados da população-alvo (GANCZAK et al, 2007;KENNEDY et al, 2009;NAGAO et al 2009;OSBORNE, 2003;TABAK;SHIAABANA;SHASHA, 2006;ZHANG et al, 2009). …”
Section: Discussionunclassified
“…Embora não tenha sido indicado pelos profissionais da presente investigação, estudos têm apontado que outra justificativa comum é estar muito ocupado no momento do acidente ou, ainda, alegar impedimentos para deixar o posto de trabalho para realizar a notificação (AU; GOSSAGE; BAILEY, 2008;AYRANCI;KOSGEROGLU, 2004;BOAL et al, 2008;GERSHON et al, 2007b;GERSHON et al 2009;KENNEDY et al 2009;SCHMID;SCHWAGER;DREXLER, 2007;SHIAO et al, 2009;SMITH et al, 2009;SOHN;EAGAN;SEPKOWITZ, 2004;WICKER et al, 2008b).…”
Section: Discussionunclassified
See 1 more Smart Citation